Teachers Strategies in Strengthening Character Education Based on Islamic Values in Online Learning During the Covid-19 Pandemic - Mawardi, Imam; Raharjo, Arif Budi; Fahm, Abdul Gafar Olawale (Universitas Muhammadiyah Magelang, 2021)
Character education based on Islamic values is one of the significant challenges teachers face in online learning during the COVID-19 pandemic. This is a crucial problem due to the numerous problems associated with the internalization of character in students. Therefore, this research aims to determine teachers' strategies to strengthen character education and the obstacles in online learning. It was carried out in Muhammadiyah Alternative Middle School (Mutual) Magelang City, Central Java Province, Indonesia. This is descriptive qualitative research with data collected through interviews, observation, and documentation. The collected data were analyzed based on teachers’ strategies in mapping the characterization of values, character analysis developed and providing solutions to the problems that arise. The results obtained the strategies developed by the teacher in strengthening character education are performed through (1) learning method innovation, (2) exemplary, (3) habituation, (4) reinforcement and sanctions, and (5) assessment. In conclusion, these strategies effectively strengthen the character values of students, including religiosity, nationalism, integrity, independence, and mutual cooperation.